Does more support mean more literacy? The relationship and mechanisms between digital support and college students’ digital literacy - Yan, Ru; Hu, Wenjing (Frontiers in Psychology, 2025)
IntroductionThe growing interest for digitization in education underscores the importance of students’ digital literacy. However, few previous studies have focused on the important role of digital support in college students’ digital literacy.MethodsGuided by the person-context interaction theory and based on a survey of 2,157 college students, this study aimed to reveal the effects of digital device support and digital technology support on college students’ digital literacy, and to further examine the mediating roles of self-efficacy and interpersonal interactions.ResultsThe results showed that both digital device support and digital technology support positively predicted digital literacy, and self-efficacy and interpersonal interaction mediated the relationship between digital device support and digital literacy. Self-efficacy mediated the relationship between digital technology support and digital literacy, while interpersonal interaction had a non-significant mediating effect in this relationship. Additionally, self-efficacy significantly predicted interpersonal interaction, forming a chain mediation effect between digital device support, digital technology support, and digital literacy.DiscussionThis study explores the relationship between digital support and digital literacy in college contexts, emphasizing the important role of individual factors in this connection. The findings contribute to a systematic understanding of how environmental factors influence individual competence, provide empirical support for digital literacy research, and offer actionable insights for improving digital literacy in higher education. It is noteworthy that the research methods used in this study were based on self-reports, which may not accurately reveal causal relationships. Future research could improve the applicability and generalizability of the findings by adopting multimodal approaches.